MRI Findings and Seizure Outcomes Compared in Focal Cortical Dysplasias Types I and II - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Preoperative clinical, neuropsychological, EEG, and imaging features and surgical outcomes of focal cortical dysplasias (FCD) types I and II were compared in 40 children with refractory epilepsy and histopathologically confirmed FCD subtypes, in a study at Charles University, Prague, Czech Republic and centers in Germany.